Effect of P-hydroxycinnamic acid in mice model of cerebral ischemia-reperfusion injury - Romgase Sakamula; Chanikarn Sakdapitak; Wachiryah Thong-asa (Penerbit Universiti Kebangsaan Malaysia, 2019)
Multiple pathomechanisms of cerebral ischemia reperfusion (I/R) injuries can be ameliorated by certain high-potential pharmaceutical substances. In the present study, we investigated the acute effect of p-hydroxycinnamic (pHCA) acid against cerebral I/R injury in mice. Thirty male ICR mice were divided into Sham, Control-I/R, and pHCA-I/R groups. The pHCA 100 mg/kg and the vehicle were given 30 min before I/R induction. Thirty-minute bilateral common carotid artery occlusion followed by 45-min reperfusion was performed on the Control-I/R and pHCA-I/R groups. Brains were collected for biochemical analysis, infarction and histological study of the cerebral cortex and corpus callosum (CC). The results showed that I/R induction significantly induced biochemical changes (p<0.05) along with the increase of brain infarction (p<0.05), percentage of degeneration in cerebral cortex (p<0.05) and decrease of CC white matter density (p<0.05). Pretreatment with pHCA significantly reduced MDA (p<0.05), brain infarction (p<0.05), cerebral cortex neuronal degeneration (p<0.05) and prevented the reduction of white matter density in the CC (p<0.05). The present study concluded that pretreatment with pHCA helps prevent cerebral I/R injury by amelioration of lipid peroxidation, white matter damage and neuronal degeneration.